Rehabilitation Concepts for Multiple Knee Ligament Injuries - Gavril GHEORGHIEVICI; Adriana Sarah NICA; Brindusa MITOIU; Delia CLANTAU; Razvan CISMASIU; Emil HARITINIAN; Cristian Ioan STOICA (Modern Medicine)
Multiple knee ligament injuries represent a significant traumatic event with an important functional prejudice which involves the injury of at least two of the four major ligaments of the knee. Management of such injury requires a thorough assessment and an interdisciplinary approach.The rehabilitation program will be constructed in accordance to the severity of the lesion and the patients expectations. The higher the goals and a more pronounced injury will results in a higher degree of involvement from the rehabilitation team. In case of cruciate ligament injury associated with a collateral ligament injury the rehabilitation program is based mostly on the same principles as for a cruciate ligament intervention, with the fi rst phase of the rehabilitation protocol being governed by an early protection phase due to the fact that early weight-bearing is considered a risk for later instability of the knee and influence over the healing tissue, while the second phase of protocol is characterised by gait restoration and maintaning balance and coordination. Multiple ligament injuries often necessitate longer rehabilitation periods, regaining full activity level being estimated at around 1 year post surgery. The purpose of the paper is to analyse the optimal modality of constructing a rehabilitation program for multiple ligament injuries and whether a consensus regarding protocol and procedures can be obtained.